The Heuristic Function of the Axiomatic Method [Abstract] - Peckhaus, Volker (Twentieth World Congress of Philosophy. Abstracts of Invited and Contributed Papers)

Ocular toxicity from ethambutol: a review of four cases and recommended precautions. - Sivakumaran, P; Harrison, AC; Marschner, J; Martin, P (N Z Med J)

Ocular toxicity from ethambutol: a review of four cases and recommended precautions. - Sivakumaran, P; Harrison, AC; Marschner, J; Martin, P (N Z Med J)

Ewald, William (Hg.), "From Kant to Hilbert. A Source Book in the Foundations of Mathematics, 2 Bde"., The Clarendon Press: Oxford/Oxford University Press: New York 1996 - Peckhaus, Volker (Mathematical Reviews)

Spectra and total energies from self-consistent many-body perturbation theory - Schindlmayr, Arno; Pollehn, Thomas Joachim; Godby, Rex William (Physical Review B)
With the aim of identifying universal trends, we compare fully self-consistent electronic spectra and total energies obtained from the GW approximation with those from an extended GWΓ scheme that includes a nontrivial vertex function and the fundamentally distinct Bethe-Goldstone approach based on the T matrix. The self-consistent Green’s function G, as derived from Dyson’s equation, is used not only in the self-energy but also to construct the screened interaction W for a model system. For all approximations we observe a similar deterioration of the spectrum, which is not removed by vertex corrections. In particular, satellite peaks are systematically broadened and move closer to the chemical potential. The corresponding total energies are universally raised, independent of the system parameters. Our results, therefore, suggest that any improvement in total energy due to self-consistency, such as for the electron gas in the GW approximation, may be fortuitous.

Systematic vertex corrections through iterative solution of Hedin's equations beyond the GW approximation - Schindlmayr, Arno; Godby, Rex William (Physical Review Letters)
We present a general procedure for obtaining progressively more accurate functional expressions for the electron self-energy by iterative solution of Hedin's coupled equations. The iterative process starting from Hartree theory, which gives rise to the GW approximation, is continued further, and an explicit formula for the vertex function from the second full cycle is given. Calculated excitation energies for a Hubbard Hamiltonian demonstrate the convergence of the iterative process and provide further strong justification for the GW approximation.

Assessment of the GW approximation using Hubbard chains - Pollehn, Thomas Joachim; Schindlmayr, Arno; Godby, Rex William (Journal of Physics: Condensed Matter)
We investigate the performance of the GW approximation by comparison to exact results for small model systems. The role of the chemical potentials in Dyson's equation as well as the consequences of numerical resonance broadening are examined, and we show how a proper treatment can improve computational implementations of many-body perturbation theory in general. Exchange-only and GW calculations are performed over a wide range of fractional band fillings and correlation strengths. We thus identify the physical situations where these schemes are applicable.

Klassische philosophische Texte von Frauen. 2nd ed

„Das Ausmaß der Trauer“ – Negativdarstellung und Engagement bei Max Frisch - Block, Iris (Literatur in Wissenschaft und Unterricht)

Die inhaltliche Dynamik des wirklichen Lebens bei Max Frisch. Zum Wandel eines Sujetbegriffs - Block, Iris (StudiaNeophilologica)

Visuelle Spezifikations- und Modellierungstechniken - Müller, Wolfgang; Sturm, Jörgen (it - Information Technology)

Wissen und Handeln: Ein Lehrbuch zur Geschichte der Ethik für den Gymnasialunterricht unter Berücksichtigung der Schriften von Philosophinnen

[Rez. v.] Francis Haskell. Die Geschichte und ihre Bilder. Die Kunst und die Deutung der Vergangenheit. Aus dem Englischen übersetzt von Michael Bischoff. Verlag C.H. Beck, München 1995 - Süßmann, Johannes (Archiv für Sozialgeschichte)

Dummett, Michael, “Introductory Remarks”, in: Czermak (Hg.) 1993 [Zbl 0836.00022], 69–76 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Spalt, Detlef D., „Exaktheit als Konstante, Begriffe im Wandel des mathematischen Denkens. Zur Analysis im 19. und 20. Jahrhundert“, in: Czermak (Hg.) 1993 [Zbl 0836.00022], 45–59 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Murawski, Roman, “On the Philosophical Meaning of Reverse Mathematics”, in: Czermak (Hg.) 1993 [Zbl 0836.00022], 173–184 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Cellucci, Carlo, “From Closed to Open Systems”, in: Czermak (Hg.) 1993 [Zbl 0836.00022], 206–220 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Maddy, Penelope, “Wittgenstein’s Anti-Philosophy of Mathematics”, in: Puhl (Hg.) 1993 [Zbl 0836.00023], 52–72 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Wang, Hao, “What is Logic?”, in: Puhl (Hg.) 1993 [Zbl 0836.00023], 11–23 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Brosch, Anette, “TLP 4.0312”, in: Puhl (Hg.) 1993 [Zbl 0836.00023], 167–172 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Synthesis of Fast On-Line Testable Controllers for Data-Dominated Applications - Hellebrand, Sybille; Hertwig, Andre; Wunderlich, Hans-Joachim (IEEE Design and Test)

Fast Self-Recovering Controllers - Hertwig, Andre; Hellebrand, Sybille; Wunderlich, Hans-Joachim (16th IEEE VLSI Test Symposium (VTS'98))

Self-Adjusting Output Data Compression: An Efficient BIST Technique for RAMs - Hellebrand, Sybille; Wunderlich, Hans-Joachim; N. Yarmolik, Vyacheslav (Design Automation and Test in Europe (DATE'98))

New Transparent RAM BIST Based on Self-Adjusting Output Data Compression - N. Yarmolik, Vyacheslav; V. Klimets, Yuri; Hellebrand, Sybille; Wunderlich, Hans-Joachim (Design & Diagnostics of Electronic Circuits & Systems (DDECS'98))

Cellucci, Carlo, “Mathematical Logic: What has it Done for the Philosophy of Mathematics?”, in P. Odifreddi (ed.), Kreiseliana, Wellesley, MA 1996 [Zbl 0894.03002], 365–388 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Delzell, Charles N., “Kreisel’s Unwinding of Artin’s Proof”, in P. Odifreddi (ed.), Kreiseliana, Wellesley, MA 1996 [Zbl 0894.03002], 113–246 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Howard, William A., “Some Proof Theory in the 1960’s”, in: P. Odifreddi (ed.), Kreiseliana, Wellesley, MA 1996 [Zbl 0894.03002], 275–288 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Odifreddi, Piergiorgio (ed.), Kreiseliana: about and around Georg Kreisel, A.K. Peters: Wellesley, MA 1996 [Zbl. 0894.03002] - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Burdman Feferman, Anita, “Kreisel on the Telephone: An Appreciation”, in: P. Odifreddi (ed.), Kreiseliana, Wellesley, MA 1996 [Zbl 0894.03002], 43–49 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Barendregt, Henk, “Kreisel, Lambda Calculus, a Windmill and a Castle”, in: P. Odifreddi (ed.), Kreiseliana, Wellesley, MA 1996 [Zbl 0894.03002], 3–14 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Feferman, Solomon, “Kreisel’s ‘Unwinding’ Program”, in: P. Odifreddi (ed.), Kreiseliana, Wellesley, MA 1996 [Zbl 0894.03002], 247–273 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Barwise, Jon, “The Right Things for the Right Reasons”, in: P. Odifreddi (ed.), Kreiseliana, Wellesley, MA 1996 [Zbl 0894.03002], 15–23 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Crick, Francis, “Georg Kreisel: A Few Personal Recollections”, in: P. Odifreddi (ed.), Kreiseliana, Wellesley, MA 1996 [Zbl 0894.03002], 25–32 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Crossley, John N., “Kreisel’s Effectiveness”, in: P. Odifreddi (ed.), Kreiseliana, Wellesley, MA 1996 [Zbl 0894.03002], 33–41 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Dyson, Freeman, “Addendum: ‘Thoughts on the Occasion of Georg Kreisel’s 70th Birthday’”, in: P. Odifreddi (ed.), Kreiseliana, Wellesley, MA 1996 [Zbl 0894.03002], 75 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Jockusch, Carl G. jun., “A Letter from Professor Kreisel”, in: P. Odifreddi (ed.), Kreiseliana, Wellesley, MA 1996 [Zbl 0894.03002], 77–78 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Morley, Michael, “Two Insights”, in: P. Odifreddi (ed.), Kreiseliana, Wellesley, MA 1996 [Zbl 0894.03002], 79–80 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

„Textuelle Verfahrensweisen in Minnespruchstrophen von Reinmar von Zweter bis Frauenlob“ - Egidi, Margreth (GRM, N.F. 48)

Platek, Richard A., “Kreisel, Generalized Recursion Theory, Stanford and Me”, in: P. Odifreddi (ed.), Kreiseliana, Wellesley, MA 1996 [Zbl 0894.03002], 97–102 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Sacks, Gerald E., “Kreisel, Generalized Recursion Theory and I”, in: P. Odifreddi (ed.), Kreiseliana, Wellesley, MA 1996 [Zbl 0894.03002], 103–108 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Nerode, Anil, “An Appreciation of Kreisel”, in: P. Odifreddi (ed.), Kreiseliana, Wellesley, MA 1996 [Zbl 0894.03002], 81–88 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Takeuti, Gaisi, “Kreisel and I”, in: P. Odifreddi (ed.), Kreiseliana, Wellesley, MA 1996 [Zbl 0894.03002], 107–109 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Weingartner, Paul, “Some Critical Remarks on Definitions and on Philosophical and Logical Ideals”, in: P. Odifreddi (ed.), Kreiseliana, Wellesley, MA 1996 [Zbl 0894.03002], 417–438 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Huber-Dyson, Verena, “Toughts on the Occasion of Georg Kreisel’s 70th Birth-day”, in: P. Odifreddi (ed.), Kreiseliana, Wellesley, MA 1996 [Zbl 0894.03002], 51–73 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Macintyre, Angus/Wilkie, A.J., “On the Decidability of the Real Exponential Field”, in: P. Odifreddi (ed.), Kreiseliana, Wellesley, MA 1996 [Zbl 0894.03002], 441–467 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Luckhardt, Horst, “Bounds Extracted by Georg Kreisel from Ineffective Proofs”, in: P. Odifreddi (ed.), Kreiseliana, Wellesley, MA 1996 [Zbl 0894.03002], 247–273 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Mints, Gregory, “Normal Forms for Sequent Derivations”, in: P. Odifreddi (ed.), Kreiseliana, Wellesley, MA 1996 [Zbl 0894.03002], 469–492 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

McCarty, David, “Completeness for Intuitionistic Logic”, in: P. Odifreddi (ed.), Kreiseliana, Wellesley, MA 1996 [Zbl 0894.03002], 301–334 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Parikh, Rohit, “Some Reminiscences of Kreisel”, in: P. Odifreddi (ed.), Kreiseliana, Wellesley, MA 1996 [Zbl 0894.03002], 89–96 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Odifreddi, Piergiorgio, “Kreisel’s Church”, in: P. Odifreddi (ed.), Kreiseliana, Wellesley, MA 1996 [Zbl 0894.03002], 389–415 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)